2015
DOI: 10.1111/itor.12178
|View full text |Cite
|
Sign up to set email alerts
|

A biased random‐key genetic algorithm for single‐round divisible load scheduling

Abstract: A divisible load is an amount W of computational work that can be arbitrarily divided into chunks and distributed among a set P of worker processors to be processed in parallel. Divisible load applications occur in many fields of science and engineering. They can be parallelized in a master-worker fashion, but they pose several scheduling challenges. The divisible load scheduling problem consists in (a) selecting a subset A ⊆ P of active workers, (b) defining the order in which the chunks will be transmitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 41 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…Biased‐randomization techniques make use of Monte Carlo simulation to enhance the performance of constructive heuristics (Faulin and Juan, ; Faulin et al., ). These techniques have been successfully employed to deal with different optimization problems, including vehicle routing problems (Fikar et al., ; Belloso et al., ), scheduling problems (Juan et al., ; Brandão et al., , ), facility‐location problems (Quintero‐Araujo et al., , ), open stacks problems (Gonçalves et al., ), and quasi‐clique problems (Pinto et al., ), among many others.…”
Section: Our Br‐ils Solving Approachmentioning
confidence: 99%
“…Biased‐randomization techniques make use of Monte Carlo simulation to enhance the performance of constructive heuristics (Faulin and Juan, ; Faulin et al., ). These techniques have been successfully employed to deal with different optimization problems, including vehicle routing problems (Fikar et al., ; Belloso et al., ), scheduling problems (Juan et al., ; Brandão et al., , ), facility‐location problems (Quintero‐Araujo et al., , ), open stacks problems (Gonçalves et al., ), and quasi‐clique problems (Pinto et al., ), among many others.…”
Section: Our Br‐ils Solving Approachmentioning
confidence: 99%
“…In our implementation, the population size was set to γ=|TOP|+|MID|+|BOT|=5×|P|, with the sizes of sets TOP,MID, and italicBOT set to 0.15×γ,0.7×γ, and 0.15×γ, respectively, as suggested in Brandão et al. (), Buriol et al. (, ), Chan et al.…”
Section: Biased Random‐key Genetic Algorithmmentioning
confidence: 99%
“…BRKGAs have been successfully used for solving many permutation based combinatorial optimization problems, see, e.g. (Duarte et al., ; Gonçalves and Resende, , , ; Gonçalves et al., ; Noronha et al., ), including the single‐round divisible load scheduling (DLS) problem (Brandão et al., ). Computational results showed that the proposed genetic algorithm outperformed a closed‐form state‐of‐the‐art heuristic (Shokripour et al., ), obtaining makespans that are 11.68% smaller on average for a set of benchmark problems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they have been used to solve different rich and realistic variants of the well-known vehicle routing problem (VRP), including the two-dimensional VRP [13], VRP variants with horizontal cooperation [14], multi-agent versions of the VRP [15], the location routing problem [16], the fleet mixed VRP with backhauls [17,18], the multi-period VRP [19], and even other versions of the multi-depot VRP [20]. BRAs have also been employed in solving other OPs, such as the single-round divisible load scheduling [21], the stochastic flow-shop scheduling [22], scheduling heterogeneous multi-round systems [23], the minimization of open stacks problem [24], the dynamic home service routing [25], waste collection management [26], or the maximum quasi-clique problem [27].…”
Section: Introductionmentioning
confidence: 99%